The Contours of Saudi Arabia-Pakistan Relations and its Impact on India - Mir, Zahoor Ahmad; Kazi, Reshmi (Asian Journal of International Affairs, 2021)
Pakistan and Saudi Arabia’s relations have been historically substantial in the economic, political, strategic, and cultural spheres. Both countries have shared diplomatic platforms at bilateral, regional, and global levels, including the Organisation of Islamic Cooperation (OIC). Saudi Arabia has traditionally been the major exporter of petroleum and a crucial market for Pakistani services and products. The study is an attempt to evaluate the recent trends and the phenomenal changes that have undergone and the dynamics of the new emerging shifts in Saudi-Pakistan relations. The worsening relations between Saudi Arabia and Pakistan provide an opportunity for India to expand its influence in the Gulf region and counter Pakistan’s narrative on Kashmir at different international forums. It has further been assumed that India seeks to materialise new opportunities for the expansion of strategic objectives while trying to reduce Saudi security dependence on Pakistan.